The Plundered Planet: Why We Must –and How We Can– Manage Nature for Global Prosperity. - Andrade, Pablo (2011)
Review of Paul Collier's book, The Plundered Planet: Why We Must –and How We Can– Manage Nature for Global Prosperity, New York: Oxford University Press, 2010.